2019
DOI: 10.3390/ijms20092280
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Indoxyl Sulfate on the Repair and Intactness of Intestinal Epithelial Cells: Role of Reactive Oxygen Species’ Release

Abstract: Chronic kidney disease (CKD) is characterized by an oxidative stress status, driving some CKD-associated complications, even at the gastrointestinal level. Indoxyl Sulfate (IS) is a protein-bound uremic toxin, poorly eliminated by dialysis. This toxin is able to affect the intestinal system, but its molecular mechanism/s in intestinal epithelial cells (IECs) remain poorly understood. This study’s aim was to evaluate the effect of IS (31.2–250 µM) on oxidative stress in IEC-6 cells and on the intactness of IECs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 64 publications
3
35
0
Order By: Relevance
“…IEC-6 cells were subsequently collected, washed with PBS, and incubated in PBS with H 2 DCF-DA (10 µM). After an incubation of 15 min at 37 °C cell fluorescence was evaluated with a fluorescence-activated cell sorter (FACSscan; Becton Dickinson, Franklin Lakes, NJ, USA), and was analyzed by CellQuest software (version 4; Becton Dickinson, Milan, Italy) [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IEC-6 cells were subsequently collected, washed with PBS, and incubated in PBS with H 2 DCF-DA (10 µM). After an incubation of 15 min at 37 °C cell fluorescence was evaluated with a fluorescence-activated cell sorter (FACSscan; Becton Dickinson, Franklin Lakes, NJ, USA), and was analyzed by CellQuest software (version 4; Becton Dickinson, Milan, Italy) [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The analytical platform developed led to detection of a higher number of tannins that were eluted in the middle and final part of the 2D plot. Several ellagic and galloyl glycosides were found, which presented a similar MS/MS fragmentation resulting from a hexose [M-H-162] - (28,29,30,32,33,34,35,38,42,48). In addition to ellagic acid hexoside (m/z 463) further monoglycosylated ellagic acid derivatives were observed, such as an ellagic acid-pentoside (m/z 433; peak 26) and deoxyhexoside (m/z 447; peaks 23, 24, 27), all of them showing the typical fragments of ellagic acid at m/z 300.…”
Section: Qualitative and Quantitative Profile Of Punica Granatum L Ementioning
confidence: 99%
“…Many studies have reported the effects of uremic toxins from the intestine. These gut-derived uremic toxins have been shown to play a pivotal role in affecting intestinal homeostasis, as well as inducing inflammation and oxidative stress in the systemic circulation [45,46]. Uremic toxins have been positively associated with NF-κB expression and exhibit positive correlations with CRP levels, iNOS and COX-2 expression [43,47].…”
Section: Oxidative Stress and Ckdmentioning
confidence: 99%
“…Several natural-derived agents have been used in Chinese herbal medicine, including flavonoids (or bioflavonoids), which form an important group of secondary plant metabolites ( Table 2). Many studies have provided evidence supporting the importance of nutrition during CKD; in particular, the role of nutrition in regulating the levels of gut-derived uremic toxins has been demonstrated to be beneficial in CKD patients [45,[123][124][125][126].…”
Section: Plant-derived Metabolitesmentioning
confidence: 99%
“…In the presence of intracellular ROS, H 2 DCF is rapidly oxidized to the highly fluorescent 2 ,7 -dichlorofluorescein (DCF). After cell treatment, previously reported, cells were collected, washed twice with phosphate buffer saline (PBS), and then incubated in PBS containing H 2 DCF-DA (10 µM) at 37 • C. After 15 min, fluorescence was evaluated using a fluorescence-activated cell sorting (BD FacsCalibur, Milan, Italy) and elaborated with Cell Quest software, as previously reported [20].…”
Section: Cell Viabilitymentioning
confidence: 99%